The translation of Care Questionnaires for Patients - Pérez Fernández, Lucila María (2020)
Care Questionnaires for patients are an important tool to assess health, both at the population and individual level. Such is the importance that this tool is acquiring, that its translation and good adaptation also become relevant. The objective of this article is to determine the linguistic and cultural validity of various questionnaires. Therefore, we have compared the original versions and the validated Spanish translations of five questionnaires that assess alcohol dependence disorders, gambling addiction, anxiety symptoms, eating behaviors and depression symptoms. This analysis has been carried out according to various linguistic, sociocultural and visual parameters. The results obtained have allowed us to develop some indications that must be taken into account when translating health questionnaires.